2007
DOI: 10.1007/s10464-007-9135-y
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood and Individual Factors in Marijuana and Other Illicit Drug Use in a Sample of Low‐income Women

Abstract: Few studies have systematically evaluated whether contextual variables differ in their ability to explain the use of different drugs in the same sample. Our objective was to examine correlates of use for different illicit drugs at the individual and neighborhood level in a tri-ethnic sample of low-income women, an underrepresented sample in drug research. Women 18-31 were recruited from a low-cost family planning clinic in southeast Texas from December 2001 to May 2003. Neighborhood level indicators of disadva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…Understanding how the neighbourhood environment or place and the specific context of the use experience relate to frequency of use can enhance knowledge of domains that can be addressed in efforts to reduce the role that crack cocaine might play in the lives of individuals situated in particular places and contexts. Perceived neighbourhood disorder was associated with an increase in frequency of use when accounting for socio-demographic characteristics, providing support for research that has found a direct link between neighbourhood disorder and illicit drug use (Boardman et al, 2001; Gibbons et al, 2004; Sunder et al, 2007). However, including crack cocaine use-related practices and the social context of crack cocaine use reduced the effect of perceived neighbourhood disorder to non-significance with having exchanged sex and people with who use occurred emerging as mediators of the effect of perceived neighbourhood disorder on frequency of crack cocaine use.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Understanding how the neighbourhood environment or place and the specific context of the use experience relate to frequency of use can enhance knowledge of domains that can be addressed in efforts to reduce the role that crack cocaine might play in the lives of individuals situated in particular places and contexts. Perceived neighbourhood disorder was associated with an increase in frequency of use when accounting for socio-demographic characteristics, providing support for research that has found a direct link between neighbourhood disorder and illicit drug use (Boardman et al, 2001; Gibbons et al, 2004; Sunder et al, 2007). However, including crack cocaine use-related practices and the social context of crack cocaine use reduced the effect of perceived neighbourhood disorder to non-significance with having exchanged sex and people with who use occurred emerging as mediators of the effect of perceived neighbourhood disorder on frequency of crack cocaine use.…”
Section: Discussionsupporting
confidence: 59%
“…However, this finding is not consistent across studies (Karriker-Jaffe, 2011). Additionally, a study of low-income women that used both an objective census measure and a measure of perceived disorder found that the objective measure indicated less disorder was associated with more drug use when comparing only the least disadvantaged neighbourhoods while perceived disorder was associated with drug use in the anticipated direction (Sunder et al, 2007). It could be that when people are experiencing similar levels of disadvantage based on income, it is the interpretation or experience of the surrounding disorder that makes them more vulnerable to drug use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…102-104 In addition, the media, advertising, and social and legal policies, have important effects on adolescent substance use and, ultimately, addiction. The influence of these cultural and ecological factors on drug use and abuse is at least in part mediated by their effects on family relationships, peer group norms, and individual-level characteristics, such as attitudes and behaviors.…”
Section: Resultsmentioning
confidence: 99%